LIPID PEROXIDATION PRODUCTS AND FREE FATTY ACIDS IN BLOOD PLASMA AND CEREBRAL SPINAL FLUID IN CHILDREN WITH CONVULSIVE SYNDROME - Rasuljon Mamasiddikovich, Shermatov (PT. Antis International Publisher, 2024)
Objective: This study aims to investigate the levels of lipid peroxidation (LP) products and free fatty acids (FFA) in children with convulsive syndrome (CS) to understand the oxidative stress associated with seizures. Method: A total of 45 children aged from several months to 1.5 years with various forms of CS were analyzed, alongside a control group of 13 healthy adults. Blood plasma and cerebrospinal fluid (CSF) were collected, and the concentrations of LP products (diene conjugates and Schiff bases) and FFA were quantified using spectrophotometric and fluorometric methods. Results: The findings revealed that children with CS exhibited significantly elevated levels of diene conjugates (810 ± 150 nmol per 1 mg lipids) and Schiff bases (42.6 ± 5.5% per 1 mg lipids) in blood plasma compared to the control group. Additionally, FFA levels in the blood plasma (2.1 ± 0.4 µg per 1 mg protein) were found to be markedly higher than those in healthy adults. These results indicate a profound increase in oxidative stress in children with CS, correlating with the duration and type of seizures. Novelty: This study highlights the critical role of oxidative stress in pediatric convulsive disorders and suggests that incorporating antioxidant therapies, such as α-tocopherol, may improve treatment efficacy in these patients. The findings provide a foundation for further research into therapeutic strategies targeting oxidative stress in pediatric neurology.